Zika vírus, microcefalia e maternidade: as experiências de mulheres no semiárido de Sergipe - Santos, Sheylla Acácio dos (2021)
This study sought to understand the daily lives of women affected by the Zika Virus in the Semi-arid Sergipe, in the municipalities of Nossa Senhora da Glória and Poço Redondo. Indepth interviews were conducted with nine women in the profile indicated above, interviews with professionals who provide care in the municipalities. Visits were made to the field, where I talked and interviewed health professionals and women, who are interlocutors of this research. The emergence of the pandemic caused by COVID-19 led to the need to adopt a perspective of digital anthropology, conducting conversations and interviews through applications. The methodology used was fieldwork, through participant observation, followed by interviews and analyses of the results obtained that were exposed in the writing of this work. During the work, the narratives are discussed using theoretical frameworks, as well as discuss the representations found in the field. The research was developed from a historical perspective and considering the social contradictions to point out the processes of social exclusion, exploitation and domination of the black population, seeking to articulate social, racial and gender inequality in the health-disease process. It is also noteworthy the feminist production of knowledge about gender relations and the denaturalisation of the inferiority of women, in addition to explaining advances and tensions between theoretical perspectives. In this context, the theory of intersectionality is presented as a theoretical and methodological framework with more possibilities of making approaches to the life experience of women.